The geopolitics of Antarctic governance: sovereignty and strategic denial in Australia's Antarctic policy. Issue 3 (3rd May 2016) - Bray, Daniel
ABSTRACT: The governance of Antarctica has re-emerged as a geopolitical issue in the past decade due to the increased presence of China, India and Russia; the continent's importance in understanding global climate change; and its economic potential as a source of marine, genetic and mineral resources. This article examines the challenges for the Antarctic Treaty System (ATS) in this context and the consequences for Australia's foreign policy in its dual role as both a territorial claimant and supporter of ATS norms of cooperative science and environmental protection. The central argument is that Antarctic 'bifocalism' is under pressure as increased commercial activity and problematic jurisdictional interfaces with other regimes create difficult regulatory challenges for the ATS and encourage assertions of sovereignty that cannot be resolved within the existing regime. Consequently, the author argues that it is vitally important for Australia to preserve the legitimacy of the ATS through a policy framework of 'strategic denial' that aims to prevent all states from acquiring sovereignty over Antarctic territory. Australia should therefore reject recent proposals to securitise Antarctic policy or pursue World Heritage listing because they involve assertions of sovereignty that risk fracturing the ATS and thus compromise Australia's enduring interest in keeping Antarctica as 'a continent of international cooperation and peace'.